Using Planar Metamaterials to Design a Bidirectional Switching Functionality Absorber—An Ultra-Wideband Optical Absorber and Multi-Wavelength Resonant Absorber - Shu-Han Liao; Chih-Hsuan Wang; Pei-Xiu Ke; Cheng-Fu Yang (Photonics, 2024)
This study aimed to investigate a bidirectional switching functionality absorber, which exhibited an ultra-wideband characteristic in one direction, while in the other direction it demonstrated the absorption of three different resonant wavelengths (frequencies). The fully layered planar structure of the absorber consisted of Al2O3, Zr, yttria-stabilized zirconia (YSZ), Zr, YSZ, Al, YSZ, and Al. The simulations were conducted using the COMSOL Multiphysics® simulation software (version 6.1) for analyses, and this study introduced three pivotal innovations. Firstly, there had been scarce exploration of YSZ and Zr as the materials for designing absorbers. The uses of YSZ and Zr in this context were a relatively uncharted territory, and our research endeavored to showcase their distinctive performance as absorber materials. Secondly, the development of a planar absorber with multifunctional characteristics was a rarity in the existing literature. This encompassed the integrations of an ultra-wideband optical absorber and the creation of a multi-wavelength resonant absorber featuring three resonant wavelengths. The design of such a multi-wavelength resonant absorber holds promise for diverse applications in optical detection and communication systems, presenting novel possibilities in related fields. Lastly, a notable discovery was demonstrated: a discernible redshift phenomenon in the wavelengths of the three resonant peaks when the thickness of YSZ, serving as the material of resonant absorber layer, was increased.